The Influence of Artificial Intelligence in Translation: Opportunities, Challenges, and Future Directions - Hajiyeva Aygun Fuad (Modern Scientific Technology, 2025)
Artificial intelligence (AI) has transformed the field of translation, enabling rapid, accessible, and scalable multilingual communication. AI-powered translation systems, particularly those based on neural machine translation (NMT), have achieved unprecedented fluency and contextual accuracy compared to earlier approaches. This paper examines the historical development of AI translation technologies, their current applications, and their advantages and limitations. Drawing on case studies of Google Translate, DeepL, and the European Union’s eTranslation platform, the article highlights both the opportunities and challenges that AI poses for linguistic diversity, cultural nuance, and ethical practice. The discussion concludes with a forward-looking analysis of potential future directions, emphasizing a hybrid model where human expertise and AI complement one another.